Calculation of chemical composition of zeolites in mordenite-clinoptilolite rocks - Кустовська, А.Д. (Proceedings of National Aviation University (archive), 2005)
Individual chemical composition of mordenite and clinoptilolite, which are both found in zeolite rocks and acid modification effect on them have been calculated. For the purpose of this study, samples of rocks of the same deposit (village Lypcha, Transcarpatia) with different content of mordenite and clinoptilolite have been used.